Hydrogeophysics - Rubin, Yoram; Hubbard, Susan S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
and Hydrogeology 1 INTRODUCTION TO HYDROGEOPHYSICS 12 SUSAN S. HUBBARD and YORAM RUBIN 1 Lawrence Berkeley National Laboratory, Earth Sciences Division, Berkeley, CA 94720 USA. sshubbard@lbl. gov 2 Department of Civil and Environmental Engineering, UC Berkeley, Berkeley, CA 94720, USA In this chapter, we discuss the need for improved hydrogeological characterization and monitoring approaches, and how that need has provided an impetus for the development of an area of research called hydrogeophysics. We briefly describe how this research area has evolved in recent years in response to the need to better understand and manage hydrological systems, provide discussions and tables designed to facilitate navigation through this book, and discuss the current state of the emerging discipline of hydrogeophysics. 1. 1 Evolution of Hydrogeophysics The shallow subsurface of the earth is an extremely important geological zone, one that yields much of our water resources, supports our agriculture and ecosystems, and influences our climate. This zone also serves as the repository for most of our municipal, industrial, and governmental wastes and contaminants, intentional or otherwise. Safe and effective management of our natural resources is a major societal challenge.
Background and Hydrogeology -- to Hydrogeophysics -- Hydrogeological Methods for Estimation of Spatial Variations in Hydraulic Conductivity -- Geostatistics -- Fundamentals of Environmental Geophysics -- Relationships between the Electrical and Hydrogeological Properties of Rocks and Soils -- DC Resistivity and Induced Polarization Methods -- Near-Surface Controlled-Source Electromagnetic Induction -- GPR Methods for Hydrogeological Studies -- Shallow Seismic Methods -- Relationships between Seismic and Hydrological Properties -- Geophysical Well Logging -- Airborne Hydrogeophysics -- Hydrogeophysical Case Studies -- Hydrogeophysical Case Studies at the Regional Scale -- Hydrogeophysical Case Studies at the Local Scale: The Saturated Zone -- Hydrogeophysical Case Studies in the Vadose Zone -- Hydrogeophysical Methods at the Laboratory Scale -- Hydrogeophysical Frontiers -- Emerging Technologies in Hydrogeophysics -- Stochastic Forward and Inverse Modeling: The (3z(BHydrogeophysical(3y (BChallenge.s
Keywords: Earth sciences; Hydrology; Geophysics; Hydrogeology; Remote sensing; Water pollution; Earth Sciences; Hydrogeology; Hydrology/Water Resources; Geophysics/Geodesy.; Remote Sensing/Photogrammetry.; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Electronic books